2017
DOI: 10.1111/papr.12586
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Japanese Version of the Fremantle Back Awareness Questionnaire in Patients with Low Back Pain

Abstract: The FreBAQ-J has acceptable psychometric properties and is suitable for use in people with LBP. Participants with high levels of disturbed body perception are well targeted by the scale. The functioning of one item (item 8) was poor. Further study is warranted to confirm if this item should be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
80
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(104 citation statements)
references
References 48 publications
18
80
5
Order By: Relevance
“…Also, the ICC score was ICC of 0.76 (95%CI 0.52–0.89), indicating the FreKAQ-J had excellent reliability–again corroborating the earlier work on the FreBAQ-J in patients with low back pain (0.81, 95% CI 0.67–0.89) [26]. To explore the reason for the slightly lower reliability of the FreKAQ-J in comparison to the FreBAQ-J we calculated ICCs of individual items in both scales.…”
Section: Discussionsupporting
confidence: 83%
“…Also, the ICC score was ICC of 0.76 (95%CI 0.52–0.89), indicating the FreKAQ-J had excellent reliability–again corroborating the earlier work on the FreBAQ-J in patients with low back pain (0.81, 95% CI 0.67–0.89) [26]. To explore the reason for the slightly lower reliability of the FreKAQ-J in comparison to the FreBAQ-J we calculated ICCs of individual items in both scales.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the SEM and MDC 95% were calculated. A MDC of at least 20% of the scale range is considered as acceptable (Chiarotto et al, 2016) Wand et al, 2016) and Japanese versions of the FreBAQ (Nishigami et al, 2017). To additionally assess construct validity of the Dutch FreBAQ within the LBP sample, the patients were subclassified into a group of patients having moderate or severe disability (based on ODI ≥ 20%) versus minimal disability (based on ODI < 20%) (Fairbank et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The items evaluate neglect-like symptoms (item 1-3), reduced proprioceptive acuity (item 4-5) and perceived trunk shape and size (item 6-9). The psychometric properties of the English (Wand et al, 2014;Wand et al, 2016) and Japanese versions (Nishigami et al, 2017) of the questionnaire have been found to be acceptable and there is consistent evidence of a significant relationship between FreBAQ scores and clinical status in a variety of lumbopelvic pain populations (Wand et al, 2014;Beales et al, 2016;Wand et al, 2016;Nishigami et al, 2017;Wand et al, 2017). A Dutch version of the FreBAQ is currently lacking, but would be useful to evaluate the Dutch-speaking LBP population, mainly located in Belgium and The Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐reported body image of the low back region was evaluated using the Japanese‐validated version of the Fremantle Back Awareness Questionnaire (FreBAQ) (0 to 36; higher scores indicate more disturbed perception). The FreBAQ is a validated scale used to assess back‐specific body perception . Participants were instructed that the questions should be answered in reference to the low back region as a whole, and modifications were made to the instructions to account for pain‐free participants .…”
Section: Methodsmentioning
confidence: 99%
“…Neuroimaging studies of people with chronic low back pain (CLBP) suggest structural and functional changes in cortical areas that are thought to subserve body perception . Several studies have reported that people with CLBP feel a sense of alienation and rejection of the back, represent the back differently when asked to draw how the back feels to them, and endorse questionnaire items associated with altered perceptual awareness of the back . Furthermore, psychophysical findings consistent with disruption of the mechanisms that underpin body image, such as decreased lumbar tactile acuity, problems localizing sensory input, poor graphesthesia performance, spatially defined tactile processing deficits, greater lumbar repositioning error, decreased lumbar motor precision, poor trunk motor imagery performance and impaired visual recognition of actions specific to the back also appear to be features of CLBP.…”
Section: Introductionmentioning
confidence: 99%